TEACHING HUMAN RIGHTS IN PAKISTANI SCHOOLS: WHAT ARE THE POTENTIAL BARRIERS? - Pirzado, Parvez Ahmed (PEOPLE: International Journal of Social Sciences, 2019)
Education plays an important role in development of any country. Education is considered one of the major contributors for developing success at local, national and global levels. Human Rights Education (HRE) promotes awareness about human rights and a way of information sharing among students, parents and the community at large, to develop skills in people to understand and combat violations of human rights. If children receive a high quality education, embedded with Human Rights concepts and principles, they can become responsible citizens and promote the human rights.Pakistan ranks at the lowest end of human development in the world. In the Human Development Index 2017, Pakistan ranks at 147th position (out of 188 countries). Pakistan is signatory to a number of international human rights Conventions and thus has pledged to protect the rights of citizens. However, recent international and national reports portray the overall human rights situation in the country as inadequate. The teaching of Human Rights is not formally included in Pakistani curricula, and there is lack of research on the subject of Human Rights Education in Pakistan.This paper attempts to explore the place of human rights within the existing policy documents and school curriculum in Pakistan and barriers in teaching human rights concepts in primary schools of Pakistan. The paper will focus on the situation of human rights education with reference to the policy documents and existing curricula of Social Studies and Islamic Studies subjects and a review of textbooks. The study seeks to identify the opportunities and constraints related to teaching of human rights concepts in schools, and possibilities of teaching human rights concepts in Pakistani schools. The paper will provide recommendations for improved practices of teaching human rights in schools. The study will provide implications for policy makers and education practitioners and will set the ground for future research. The study will also suggest further research human rights education in Pakistan.